2018
DOI: 10.1186/s12885-018-5120-0
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600E mutation and 9p21: CDKN2A/B and MTAP co-deletions - Markers in the clinical stratification of pediatric gliomas

Abstract: BackgroundGenetic alterations in pediatric primary brain tumors can be used as diagnostic and prognostic markers and are the basis for the development of new target therapies that, ideally, would be associated with lower mortality and morbidity. This study evaluates the incidence and interplay of the presence of BRAF V600E mutation and chromosomal 9p21 deletions in a series of 100 pediatric gliomas, aiming to determine the role of these alterations in recurrence and malignant transformation, and to verify if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
(19 reference statements)
1
21
0
1
Order By: Relevance
“…In BRAF V600E, TP53, or IDH1 altered tumors, concurrent CDKN2A/B deletions portend a worse prognosis. 49,50 Several ongoing clinical trials are exploring the role of targeted therapeutics in pediatric brain tumors. BRAF, MEK, PD-1, and CTLA-4…”
Section: Discussionmentioning
confidence: 99%
“…In BRAF V600E, TP53, or IDH1 altered tumors, concurrent CDKN2A/B deletions portend a worse prognosis. 49,50 Several ongoing clinical trials are exploring the role of targeted therapeutics in pediatric brain tumors. BRAF, MEK, PD-1, and CTLA-4…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic changes in tumors, especially those relating to polyamines metabolism, demonstrate that many mechanisms underlying MTAP function need to still be clarified [35,36]. In gliomas, loss of MTAP locus is also frequently reported [37][38][39][40][41]. Nevertheless, the clinical and the biological impacts of MTAP are poorly explored in gliomas [37,38,42].…”
Section: Introductionmentioning
confidence: 99%
“…BRAF‐V600‐ mutation was found in 18% of the tumors of our cohort, and was reported at variable frequencies up to 25% for pediatric DG2 6,10,14,15,23,47,48 . Although the presence of this mutation was rated as unfavorable with more frequent non‐response to adjuvant treatment and shorter PFS in the basket group of LGG, 14,23 no specific data are available for DG2.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, re‐biopsy of recurrent or progressing lesions is warranted even in early progression. Malignant transformation of pediatric LGG has been shown for BRAF‐V600E ‐mutated tumors and was linked to the concurrent presence of CDKN2A ‐deletion 6,23,48,49 . Although the underlying molecular alteration was already traced in the initial biopsy in the report of Mistry et al, 49 and identical genetic alterations were found in primary and recurrent tumors in the series of Bergthold et al, 47 its later evolution cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%